Kajian Formulasi Sediaan Floating Drug Delivery System (FDDS) Pada Pengobatan Infeksi Helicobacter pylori - Siti Anggina Ismiyati Solihat; Sani Ega Priani; Anan Suparman (UNISBA Press, 2023)
Abstract. Floating drug delivery system (FDDS) is a drug delivery system that can increase the residence time in the stomach. This delivery system was developed to increase the effectiveness of treatment of H. pylori infection, by extending the contact time with the mucosa (target), through the mechanism of floating in gastric fluid. This study aims to assess the formulation of FDDS preparations for the treatment of H. pylori infection. In this study, a systematic literature review was conducted from reputable articles based on inclusion and exclusion criteria. From this study, several conclusions were obtained that FDDS preparations have been developed on the active substances amoxycillin, clarithromycin, ciprofloxacin, metronidazole, and levofloxacin. Formulations using effervescent and non-effervescent systems meet the requirements of a good FDDS preparation, which has a floating lag time of <60-600 seconds and a floating time of >12 hours. The most widely used polymers were sodium alginate and HPMC. Abstrak. Floating drug delivery system (FDDS) merupakan sistem penghantaran obat yang dapat meningkatkan waktu tinggal di lambung. Sistem penghantaran ini dikembangkan untuk meningkatkan efektivitas pengobatan infeksi H. pylori, dengan cara memperpanjang waktu kontak dengan mukosa (target kerja), melalui mekanisme mengapung di cairan lambung. Penelitian ini bertujuan untuk melakukan pengkajian mengenai formulasi pada sediaan FDDS untuk pengobatan infeksi H. pylori. Dalam penelitian ini dilakukan systematic literatur review yang bersumber dari artikel bereputasi berdasarkan kriteria inklusi dan eksklusi. Dari penelitian ini didapatkan beberapa kesimpulan bahwa sediaan FDDS telah dikembangkan pada zat aktif amoxycillin, claritromycin, ciprofloxacin, metronidazol, dan levofloxacin. Formulasi dengan menggunakan sistem effervescent dan non-effervescent memenuhi persyaratan sediaan FDDS yang baik, yaitu memiliki floating lag time <60-600 detik dan floating time >12 jam. Polimer yang paling banyak digunakan adalah sodium alginat dan HPMC.